Application of the VDI 2221 method in the design of 3D printer machines utilizing additive manufacturing technology - Irwan, Hery; Fattah, Muhammad Rusydi; Tarigan, Ryan Dana Gidion; Aritonang, Fauzan Maulana Siddiq; Sumarya, Edi (OPSI, 2025)
In the era of Industry 4.0, digital transformation integrates advanced technologies such as the Internet of Things (IoT), artificial intelligence, and data-driven manufacturing, driving advancements in science and technology. Within this framework, this study focuses on the design and fabrication of a cantilever-type 3D printer aimed at producing a prototype capable of efficient and functional 3D object printing. Additive Manufacturing (AM) technology, particularly Fused Deposition Modeling (FDM), enables the conversion of digital designs into physical products through the layer-by-layer deposition of material. The 3D printer is designed using the VDI 2221 methodology, which encompasses four key phases: task clarification, conceptual design, embodiment design, and detailed design. A key consideration during the design process is the use of filaments derived from plastic bottle waste to mitigate environmental impact. The results identify the Cartesian model variant (Variant 1) as the optimal solution, selected based on functional performance, cost efficiency, and ease of assembly. This machine achieves nozzle temperatures up to 270°C and bed temperatures up to 80°C, with a total production cost of Rp 3,657,000.00. These findings demonstrate the potential of 3D printing technology to advance plastic waste recycling and promote the development of more sustainable 3D printing solutions.